An alternative way to measure respiration induced changes of circumferences: a pilot study - Laufer, B.; Krueger-Ziolek, S.; Docherty, P. D.; Hoeflinger, F.; Reindl, L.; Moeller, K. (2020 42nd Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2020)
Various measurement systems can be used to obtain dynamic circumferences of the human upper body, but each of these systems has disadvantages. In this feasibility study we introduce a non-invasive and wearable thoracic belt to measure dynamic changes of circumferences of thorax or abdomen. To evaluate this approach, five subjects undertook various breaths of disparate tidal volumes, which were measured by the belt and simultaneously by a motion capture system which provided a reference metric. The results of the belt concurred with the reference system. A coefficient of determination (adjusted R 2 ) of 0.99 and a mean squared error of less than 0.87 mm 2 showed that the belt is capable of measuring changes accurately and a couple of respiratory parameters, such as the respiratory rate, can be obtained. Clinical Relevance-The introduced system links surface motions of the upper body with the underlying respiratory mechanics. Thus it provides some respiratory parameters without the disadvantages of a facemask or a mouthpiece. The system could allow the analysis of breathing status in some clinical applications and could be used for low-cost monitoring in homecare or to analyse respiratory parameters during sports.